Editorial - Cock, I.E. (Pharmacognosy Communications)
Dear readers and authors, I am pleased to bring you volume 7, issue 1 of Pharmacognosy Communi cations. The metrics of Pharmacognosy Communications continue to improve. In my editorial in the previous issue, I summarised the achieve ments of the journal to that point. By the end of 2015, Pharmacognosy Communications had published 153 manuscripts with 591 total cita tions, at an average citation rate of 3.86 per published manuscript across that period. Since then, we have received further promising journal met rics. The website Researchgate recently reported the 2015 journal impact of Pharmacognosy Communications to be 2.19 (Figure 1a). Whilst this is not an official ISI impact factor, it is calculated in a similar manner (publication number during a time period/ total citations across that period). Indeed, it is likely that this figure may be underestimated as the Researchgate impact metric is calculated using Researchgate data (which uses citations reported on that site only). This is a very good result for Pharmacognosy Communications. Whilst it must be emphasised that this is not an official Thompson and Reuters impact factor, it does indicate that the journal is developing as a credible forum in the pharmacognosy, phytotherapy and traditional medicine fields. We are currently ranked by Research gate as having a similar impact as the Journal of Ethno pharmacology (2.69), Phytochemistry (2.27), Phytomedicine (2.08) and Phytotherapy Research (2.65) (Figure 1 a). These journals are highly respected and are considered as being leaders in their fields, indicting the impact that Pharmacognosy Communications has achieved. Notably, those journals have a much longer history than Pharmacognosy Commu nications, each being in print for at more than 20 years. Indeed, the Journal of Ethnopharmacology has been published since 1979. As journal impact is a measure of the total citations over a time period (rather than citations from publications from that time period only), citations for older publications will contribute to journal impact metrics. Thus, journals which are well established would be expected to have higher impacts due to the contribution of the older, as well as recent publications. Fig ure 1b shows the trend towards increasing impact for Pharmacognosy Communications over the 3 year period in which we have been ranked by Researchgate. It is reasonable to expect that the impact will continue to steadily improve in future years, as we grow and accumulate a larger publication backlog.